2023
DOI: 10.3390/ijerph20043061
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Use and the Perceived Risk of COVID-19: Patient Experience

Abstract: Introduction: The COVID-19 outbreak resulted in an increased demand for telemedicine worldwide. Telemedicine is a technology-based virtual platform that allows the exchange of clinical data and images over remote distances. This study aims to examine the impact of the perceived risk of COVID-19 on telemedicine use in Bangladesh. Methods: This explanatory study was conducted in hospital settings across Dhaka city in Bangladesh. Patients were eligible to participate if they were aged 18 years or over and had use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Medicine, Obstetrics, Gynecology, Pediatrics, and Dermatology queries are mainly addressed by TM services 27 . Another study demonstrated that TM was mostly used for Radiotherapy, General Medicine, and Cardiology-associated consultations 34 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicine, Obstetrics, Gynecology, Pediatrics, and Dermatology queries are mainly addressed by TM services 27 . Another study demonstrated that TM was mostly used for Radiotherapy, General Medicine, and Cardiology-associated consultations 34 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…During the peak of COVID-19, COVID-19 related questions were asked almost threefold (5.5% from January to 16.2% in March) 11 . TM is mostly chosen to avoid physical contact 34 , although no physical examination is required in follow-up cases of chronic illnesses 42 . Less educated people were more concerned about the authenticity of a diagnosis, as there was no facility for a physical examination 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such patients may necessitate additional interventions, such as blood transfusions or treatments for their underlying conditions [ 71 ]. Telemedicine and remote monitoring represent valuable modalities for managing COVID-19 patients, especially those with mild or moderate symptoms not requiring hospitalization, thereby mitigating transmission risk while ensuring appropriate care delivery and alleviating strain on healthcare systems [ 72 ].…”
Section: Reviewmentioning
confidence: 99%
“…Wu et al [ 7 ] studied telemedicine in Taiwan and found it is less popular among older and less educated people due to perceived social and psychological risks. Hosseinzadeh et al [ 8 ] show how telemedicine in Bangladesh was perceived as satisfactory during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%